Natural designer solvents for greening analytical chemistry - Espino, Magdalena Belén (2016)
Developing new green solvents is one of the key subjects in Green Chemistry. Ionic liquids and deep eutectic solvents were discovered as an option to replace organic solvents. However, ionic liquids and deep eutectic solvents (DES) have still some limitations to be applied to real chemical industry. In this sense, a new generation of designer solvents have emerged in the last decade as promising green media. When the compounds that constitute DES are primary metabolites, namely, aminoacids, organic acids, sugars, or choline derivatives, DES are called Natural Deep Eutectic Solvents (NADES). NADES fully represent green chemistry principles. These solvents offer many striking advantages including biodegradability, low toxicity, solute stabilization, sustainability, low costs and simple preparation. Thus, interesting applications in health-related areas can be proposed. This review presents an overview in order to up-to-date knowledge regarding NADES with special emphasis on their analytical applications and further perspectives as truly green solvents.